Pertrochanteric hip fracture is associated with mobility decline and poorer physical performance 4 to 6 months post-hip fracture - Kujala Minna A.; Hongisto Markus T.; Luukkaala Tiina; Stenholm Sari; Nuotio Maria S. (BioMed Central Ltd., 2025)
Background: To study the effect of hip fracture type on physical performance, functional ability and change in mobility four to six months after the injury.
Methods: A total of 1331 patients out of consecutive 2052 patients aged ≥ 65 years who underwent hip fracture surgery were included in the study. Patient information was collected on admission, during hospitalization, by phone interview and at the geriatric outpatient clinic 4 to 6 months after the fracture. Of the 1331 eligible patients, Grip strength, Timed Up and Go -test (TUG), Elderly Mobility Scale (EMS), mobility change compared to pre-fracture mobility level, Basic Activities of Daily Living (BADL) and Instrumental Activities of Daily Living (IADL) were used to determine physical performance and functional ability. Logistic regression was used for the analyses which was adjusted for gender, age, American Society of Anesthesiologists score, diagnosis of cognitive disorder, pre-fracture living arrangements, mobility and need of mobility aid.
Results: Patients with pertrochanteric hip fracture had an EMS lower than 14 (Odds Ratio (OR) 1.38, 95% confidence intervals (CI) 1.00-1.90), TUG time ≥ 20 s (OR 1.69, 95% CI 1.22-2.33) and they had declined in mobility (OR 1.58, 95% CI 1.20-2.09) compared to femoral neck fracture patients 4 to 6 months post-hip fracture in multivariable-adjusted logistic regression analyses. Grip strength and functional ability (IADL, BADL) 4 to 6 months after hip fracture did not differ between fracture types. There were no statistically significant differences in physical performance in patients with a subtrochanteric fracture compared to patients with a femoral neck fracture.
Conclusions: Pertrochanteric hip fracture independently associated with poorer physical performance 4 to 6 months post hip fracture compared to other hip fracture types. Pertrochanteric hip fracture patients should be given special attention in terms of regaining their previous level of mobility.
Keywords: Disability; Femoral neck fracture; Geriatric assessment; Hip fracture; Mobility; Muscle strength; Orthogeriatric care; Pertrochanteric fracture; Physical performance; Subtrochanteric fracture.